A Legal Analysis of Paternity Leave Rights Policy in Law Number 4 of 2024 from a Gender Justice Perspective - Najma Fadhilatul Sabbichis; Tri Sulistiyono (Semarang State University Undergraduate Law and Society Review, 2025)
This study examines the paternity leave policy as stipulated in Law Number 4 Year 2024 on Maternal and Child Welfare with a gender justice approach. While the law provides leave for male workers to accompany their wives, the duration of leave available is limited and does not fully reflect the principle of gender equality. This study examines the legal aspects of the paternity leave provision, including comparing it with similar policies in other countries and identifying implementation constraints caused by patriarchal culture and unequal treatment between workers in the public and private sectors. The findings show that the paternity leave policy in Law No. 4 of 2024 needs to be expanded both in terms of time and scope in order to increase the active role of fathers in childcare and support the creation of gender equity in the work and family environment. This study recommends more comprehensive and inclusive policy reforms, as well as cultural change efforts to remove traditional gender stigmas that hinder the effective implementation of paternity leave.